2003
DOI: 10.1002/hup.504
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of aggression and violence

Abstract: The pharmacological management of violence and aggression is a common and substantial clinical dilemma in the emergency psychiatric situation. A literature search was conducted through PubMed and using the Cochrane Library. This was followed by a manual search of selected literature. Randomised controlled trials were sought that specifically addressed the acute situation, rather than the ongoing management of chronic conditions. There was a paucity of well-controlled data and insufficient evidence to support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…Such interventions have been common in psychiatry for aggressive patients. Yet, recent reviews of randomized control studies have revealed only a weak effect (Goedhard et al, 2006;Humble and Berk, 2003). More optimistic findings exist where particular DSM disorders, with accompanying aggression, are targeted.…”
Section: Pharmacological Interventionsmentioning
confidence: 92%
“…Such interventions have been common in psychiatry for aggressive patients. Yet, recent reviews of randomized control studies have revealed only a weak effect (Goedhard et al, 2006;Humble and Berk, 2003). More optimistic findings exist where particular DSM disorders, with accompanying aggression, are targeted.…”
Section: Pharmacological Interventionsmentioning
confidence: 92%
“…67,68 The more recently developed so-called atypical neuroleptics are measured in terms of their efficacy, potency, and selectivity relative to the traditional so-called typical compounds such as haloperidol and chlorpromazine which were introduced five decades ago and still serve as benchmarks for comparison. [69][70][71] A critical principle governing the pharmacotherapeutic approach to managing violent and aggressive individuals is the behavioral specificity through which these drugs reduce aggressive behavior. 18,72,73 The first-generation phenothiazines, butyrophenones and thioxanthenes, lower aggressive outbursts in a dose range that also engenders significant sedation and other side effects, and this unfavorable profile of drug action has led to the label of "chemical restraint" for these treatments.…”
Section: Dopamine and Serotonin: Typical And Atypical Neurolepticsmentioning
confidence: 99%
“…In this respect, aggression is viewed as an adaptation that can have key effects on the lifelong success of individuals and that conveys evolutionary fitness [2]. In humans, expression of aggression out of the appropriate context is, in contrast, currently recognised as one of the greatest and most challenging problems in society and has been identified as a key area for research and pharmacological intervention [3,4]. Despite the impacts of aggression in social systems and the plethora of studies in this area, its neurophysiological basis is not well understood in any species.…”
Section: Introductionmentioning
confidence: 99%